TOLERANCE TO UNCERTAINTY IN THE CHARACTERISTICS OF ENVIRONMENTAL AND PERSONAL ADAPTATION RESOURCES OF THE POPULATION OF MOUNTAIN REGIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The adaptation of residents of mountainous areas is influenced by both the diversity of climatic, socio-economic conditions of these territories, and the personal characteristics (tolerance of uncertainty - TN, intolerance to uncertainty ITN) of the population. This determines the relevance of studying the environmental and personal resources of the population of mountainous areas in the process of adaptation. The purpose of the work was to specify the relationships between level-by-level properties, to wit, personal - (TN) and (ITN), assessed using the S. Badner questionnaire (modified by T.N. Kornilova, M.A. Chumakova) and environmental characteristics (method for self-assessment of needs satisfaction existential, social, development - V.N. Edronova, N.V. Solovyova, 2011) in the settlements of Tyup, At-Bashi. A correlation analysis of these parameters was considered with the calculation of the Spearman correlation coefficient using the SPSS 16 program. 302 respondents living in the high-mountain Naryn region (At-Bashi), and 154 in the mid-mountain Issyk-Kul regionи(Tyup) were examined. General and specific aspects of the assessed relationships were analyzed. The general features of relationships in regional centers are represented by the presence in them of powerful correlations between environmental resources, as an expression of their demand by the population. Also, a common feature was a few of connections between level-by-level resources: in Tyup, individual environmental resources (development, social) were connected with TN, ITN; in At-Bashi – individual existential and social environmental resources were included in these relationships. The differences concerned the presence of negative level-by-level relationships in Tyup, compared with positive correlations of environmental-personal resources in At-Bashi, which we interpret by the variety of approaches and semantic assessment of reality in the organization of their activity by the population.
Keywords: tolerance of uncertainty, intolerance to uncertainty, population of mountain regions, adaptation, life needs, comparative analysis